2022
DOI: 10.1093/hropen/hoac058
|View full text |Cite
|
Sign up to set email alerts
|

Predicting serum hormone concentration by estimation of urinary hormones through a home-use device

Abstract: STUDY QUESTION Can a home-use device be used to predict serum hormone levels? SUMMARY ANSWER A home-use device can predict urinary hormone values which are well correlated to serum concentrations of respective hormones and hence can be used as a proxy for serum measurements WHAT IS KNOWN ALREADY Home-use devices that predict ovulation are calibrated against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In addition, a recent study published in 2023 compared E2, progesterone and LH concentrations to E3G, PdG and LH in urine. A correlation of 0.96, 0.95 and 0.98 allowed researchers to conclude that the use of urine tests instead of blood is acceptable whenever testing is required [14]. These results indicate that LFAs are accurate alternatives to blood sampling that are more convenient, painless, eliminate the need for venipuncture, and can be completed at home on a regular basis.…”
Section: Lateral Flow Immunoassays' Performancementioning
confidence: 89%
“…In addition, a recent study published in 2023 compared E2, progesterone and LH concentrations to E3G, PdG and LH in urine. A correlation of 0.96, 0.95 and 0.98 allowed researchers to conclude that the use of urine tests instead of blood is acceptable whenever testing is required [14]. These results indicate that LFAs are accurate alternatives to blood sampling that are more convenient, painless, eliminate the need for venipuncture, and can be completed at home on a regular basis.…”
Section: Lateral Flow Immunoassays' Performancementioning
confidence: 89%
“…Prior research has demonstrated that many period tracker apps provide conflicting information on an ovulation day and a fertile window [ 4 , 6 , 26 ]. Several consumer-available tracking technologies are in the early stages of reliability testing for tracking or confirming ovulation [ 7 , 13 , 27 , 28 ]. More research is needed to validate their use for family planning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to smartphone apps and temperature tracking devices, there has been significant growth in the development of at-home urine hormone testing devices that can measure multiple reproductive hormone levels across the menstrual cycle. Direct-to-consumer urine hormone testing devices include, but are not limited to, the Clearblue ® Fertility Monitor [ 11 ], Proov ® [ 12 ], Inito Fertility Monitor [ 13 ], Mira ® Fertility Tracker [ 14 ], and Oova™ Fertility Tracker [ 15 ]. Prior to these technologies, it was neither feasible nor cost-effective to measure hormone levels at multiple timepoints throughout the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…IFM uses a multi-scale algorithm to detect the device and eliminate the variations in resolution and aspect ratio due to smartphone variability 11 . A recent study has also shown that urine metabolite measurements by IFM are well correlated with their respective serum hormones 30 .…”
Section: Introductionmentioning
confidence: 90%